2021
DOI: 10.4103/njcp.njcp_52_21
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, pattern, and treatment of nose fractures

Abstract: Background: Determining the etiology, epidemiology, pattern, and treatment of nasal bone fractures and the associated soft tissue injuries in a population will be beneficial for the prevention, rapid and correct diagnosis, and adequate management of this pathology in order to minimize postoperative complications. Patients and Methods: This study retrospectively evaluated the patients admitted and treated for nasal bone fractures in a university clinic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Regarding this, the literature reports the fact that injury due to a blow with a fist more frequently results in mandibular fractures or zygomatic bone disjunction, while road traffic accidents and firearm or explosive injuries predominantly lead to midface, comminuted or panfacial fractures ( 3 - 6 , 10 - 12 ). The high incidence of maxillofacial injuries by fist blows, as well as the legislative norms that forbid possession of firearms in our geographical area can explain the great number of mandibular fractures registered in this study ( 13 ). In the midface, zygomatic bone fractures had the highest incidence in the present study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Regarding this, the literature reports the fact that injury due to a blow with a fist more frequently results in mandibular fractures or zygomatic bone disjunction, while road traffic accidents and firearm or explosive injuries predominantly lead to midface, comminuted or panfacial fractures ( 3 - 6 , 10 - 12 ). The high incidence of maxillofacial injuries by fist blows, as well as the legislative norms that forbid possession of firearms in our geographical area can explain the great number of mandibular fractures registered in this study ( 13 ). In the midface, zygomatic bone fractures had the highest incidence in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…The interrelationship between orbital fractures and zygomatic bone fractures is well known, the zygomatic bone being part of 2 of the 4 orbital walls [1][2][3][4][5] . In this context, these two categories mostly overlap; authors may include orbital fractures in the category of zygomatic bone fractures and vice versa 13 . For example, in this study, frontozygomatic fracture was included in the category of zygomatic bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A study that analyzed the clinical patterns and characteristics of midfacial fractures over a period of 10 years, this time in the western Romanian population, found that the most common types of fracture were laterofacial (50%) and nasal bone fractures (22.93%), with LeFort type fractures being the least encountered, representing 0.83% for LeFort type I, 1.03% for LeFort Type II and 0.83 for LeFort type III from a total of 397 patients [ 13 ]. Another study from the same part of the country found that midface fractures affect most commonly the male sex and patients from the urban area (54.35%) aged between 20 and 29 years old, with the most incriminated etiology being assault, followed by fall trauma and road traffic accidents [ 14 ]. The fact that the second most incriminated etiology from the north-eastern part of the country is road traffic accidents, and for the western part is accidental falls could be explained by a more developed transport infrastructure in the western part of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is among the main causes of death and morbidity in the world, according to data from the World Health Organization, and is considered a public health problem [ 1 , 2 ]. Injuries to the head and face may be responsible for 50% of all traumatic deaths when associated with other injuries such as cervical, abdominal, thoracic, and brain trauma according to more recent research [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%